Dependency of B-1 Cells in the Maintenance of Splenic Interleukin-10 Producing Cells and Impairment of Macrophage Resistance in Visceral Leishmaniasis - Angélica Fernandes Arcanjo; Dirlei Nico; Gabriellen Menezes Migliani de Castro; Yasmin da Silva Fontes; Paula Saltarelli; Debora Decote-Ricardo; Marise P. Nunes; Antônio Ferreira-Pereira; Clarisa B. Palatnik-de-Sousa; Célio G. Freire-de-Lima; Alexandre Morrot; Alexandre Morrot (Frontiers in Microbiology, 2017)
Visceral leishmaniasis is a neglected disease caused by Leishmania protozoa parasites transmitted by infected sand fly vectors. This disease represents the second in mortality among tropical infections and is associated to a profound immunosuppression state of the host. The hallmark of this infection-induced host immunodeviation is the characteristic high levels of the regulatory interleukin-10 (IL-10) cytokine. In the present study, we investigated the role of B-1 cells in the maintenance of splenic IL-10 levels that could interfere with resistance to parasite infection. Using an experimental murine infection model with Leishmania (L.) infantum chagasi we demonstrated an improved resistance of B-1 deficient BALB/XID mice to infection. BALB/XID mice developed a reduced splenomegaly with diminished splenic parasite burden and lower levels of IL-10 secretion of purified splenocytes at 30 days post-infection, as compared to BALB/c wild-type control mice. Interestingly, we found that resident peritoneal macrophages isolated from BALB/XID mice were more effective to control the parasite load in comparison to cells isolated from BALB/c wild-type mice. Our findings point to a role of B-1 cells in the host susceptibility to visceral leishmaniasis.